MuSK-antibody-positive myasthenia gravis in a South Asian population. - Chang, T; Gunaratne, P; Gamage, R; Riffsy, M; Vincent, A (2009)
BACKGROUND: MuSK-antibody-positive myasthenia gravis (MuSK-MG) is diagnosed in 0-40% of cases with generalized seronegative MG in different populations. The presence of anti-MuSK antibodies defines a distinct clinico-immuno-pathological subtype of MG. We analysed for the first time the serology and clinical characteristics of MuSK-MG in a South Asian population. METHODS: 113 patients with MG attending Neurology Units in three state hospitals in the district of Colombo, Sri Lanka were studied. AChR antibodies were tested in all patients whilst MuSK antibodies were tested in patients seronegative for AChR antibodies. Sera from patients with other neurological diseases (OND) concurrently attending the same hospitals were obtained as controls. RESULTS: Four of 19 AChRAb-negative generalised MG patients (21%) were positive for MuSKAbs. Two were women and in 3, disease onset was before the age of 30 years. Although 3 of 4 had ocular-bulbar involvement at presentation, none had facial or bulbar muscle wasting. Two of the 4 patients (50%) had developed myasthenic crisis and had required ventilation. A good treatment outcome appears to be related to early commencement of immunosuppressive medication. None of the patients with ocular MG or OND were positive for either AChR or MuSK antibodies. CONCLUSIONS: MuSK-MG is seen in about a fifth of generalised seronegative MG patients in Sri Lanka. The clinical characteristics are consistent with features described in Caucasian MuSK-MG patients.